Suburban Sustainability Index: An Approach to Assess Suburban Sustainability in Metropolitan Jakarta, Indonesia - Yandri, Pitri; Priyarsono, Dominicus Savio; Fauzi, Akhmad; Dharmawan, Arya` Hadi (Universitas Diponegoro, Indonesia, 2020)
In the arena of academic discourse, there is a kind of ‘dissatisfaction’ over the indicators of sustainability. Although Indonesia has formally adopted its sustainable development indicators from the United Nations, the research to find compatible indicators for certain contexts still to continues. There are hundreds and/or even thousands of reports tell us the new indicators of sustainability with various methods and approaches. But very few are paying attention to – or at least – building sustainability indicators of suburban areas, especially the metropolitan suburbs of Jakarta. Therefore, this study tried to develop a typical suburban sustainability indicator called the Suburban Sustainability Index (SSI). As an empirical case, we observe four suburbs which located in hinterland of Metropolitan Jakarta: South Tangerang City, Tangerang City, Depok, and Bekasi. Based on the three dimensions of sustainability (social, economic, and environment), we developed 30 indicators and tested them with Min-Max analysis. More than that, we also conduct Index Analysis to assess the sustainability status of the four suburbs. We found that three regions were less sustainable, and one region was quite sustainable. Further elaboration on these findings is presented in this article.